ANALISIS KARAKTERISTIK PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN DALAM SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2019 - Andi Sayyidatun Ufairah Anto; Darwis Said; Aini Indrijawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Social responsibility is included in the fields of economics, law, ethics that must be fulfilled in order to fulfill the expectations of stakeholders. Disclosure of social responsibility is done so that the company achieves the desired profit in order to improve the environmental economy. In order to provide feedback to the environment, companies are required to implement CSR. This includes companies in the telecommunications sector that are required by the government to implement CSR. This is regulated in Law number 4 of 2009 article 108 paragraph (1). This study uses a deductive-quantitative approach. The TLKM company as a registered telecommunications company has complied with Law Number 40 of 2007 concerning Limited Liability Companies article 74 which requires companies engaged in natural resources to carry out social responsibility. However, the disclosures made by most of the listed telecommunication companies are still minimal. In fact, the graphics are still unstable. However, related to corporate social responsibility carried out by TLKM, it is quite large with an average of more than 400 billion. In addition, TLKM also saves water and energy use in the productivity of its company.